The effect of the surface condition of Aluminium ingot (AA3003) during roll bonding with clad Aluminium alloy (AA4045) to form an Aluminium brazing material - Mutsakatira, Innocent (Department of Mechanical Engineering, 2021)
Hulamin is the leading producer of aluminium products in South Africa. One of the products made at Hulamin is the aluminium brazing sheet. The aluminium brazing sheet is made from two aluminium alloys, AA3003 and AA4045. The main alloying element in the 3XXX series alloy is manganese and the main alloying element in the 4XXX series alloy is silicon. An aluminium brazing sheet is manufactured during an industrial process called “accumulative roll bonding”, where AA4045 is termed “the clad” and AA3003 “the core”. The two materials are stacked together with the core sandwiched between two clad layers. Before the materials are stacked together, they undergo surface preparation. At Hulamin, the surface roughness of the core is kept at 10 µm and the surface roughness of the clad at 1 µm. After surface preparation, the stacked material is put into a hot rolling mill, where it undergoes reduction through several passes until it reaches the desired gauge. The aim of this project is to determine the effect of the surface roughness of both the clad and the core on the quality of the bond after roll bonding. While the relevant literature specifies that an increase in surface roughness increases bond strength, the current set surface finishes being implemented at Hulamin have been obtained through trial and error, with no validated experimental work to support them. This research aims to find the optimum surface finish in order to streamline the process of surface preparation. A design matrix was constructed based on the surface finish being used at Hulamin, where the core was at 10 µm and the clad at 1 µm. Fourteen surface conditions were formulated and three tests were performed on each surface condition. The samples were manually ground on different grit papers to an average surface roughness of 0.5 µm, 1 µm and 3 µm for the clad and 7 µm, 10 µm, 15 µm and 25 µm for the core. Simulation of the hot rolling at the University of Cape Town's (UCT's) Centre for Materials Engineering (CME) laboratory was achieved using plane strain compression testing (PSC) on the Gleeble 3800. The PSC sample geometry of 30 mm x 50 mm x 10 mm was achieved by stacking a 5 mm sample from the clad liner plate and a 5 mm thick sample from the as-cast core material. To simulate the hot roll bonding the tests were run at 450 ºC at a strain rate of 1.5 s-1 . The test parameters were obtained from the Hulamin mill log data. In order to assess the strength of the bond, post PSC test, tensile shear testing was performed on specimens wire-cut from the gauge of the deformed PSC sample. The tensile shear specimens were designed according to ASTM D3165. The tensile shear tests were performed on a Zwick Universal Testing machine, in conjuction with single-camera Digital Image Correllation (DIC). The purpose of the DIC was to monitor the strain localisation at the interface. The tensile test was run at 0.0012 mm/min at room temperature. The shear test results confirmed that surface roughness played a major role in the bond strength formed between these two dissimilar materials. It was found that the Hulamin benchmark surface preparation, set at 10 µm and 1µm, could be improved by increasing the surface roughness of the core to 15µm while keeping the clad surface finish constant. The rolling direction (RD) of the specimen was cut, mounted and polished for microstructural feature characterisation, using light microscopy and scanning electron microscopy (SEM) with backscattered electron (BE) imaging. In order to characterise the bond further, energydispersive X-ray spectroscopy (EDS) was performed across the interface of the samples to show the diffusion of Si. Microstructural analysis revealed that a poor bond resulted in the presence of large voids, while a high integrity metalurgical bond contained very small voids. Also, a good metallurgical bond allowed for the diffusion of Si across the bond, although these results were qualitative because diffusion of Si across the interface is largely time- and temperature-dependent. Combined strain and microstructural results showed that finer surface roughnesses yielded poorer bonds because of minimal frictional force and that rougher surface finishes also yielded poorer bonds, owing to larger troughs on the surface of the material that led to void formation at the interfaces, which in turn caused sites of delamination. There had to be an optimum surface finish that existed between the two alloys where the finish would obtain a metallurgical bond that was of optimum strength. Should this optimum finish be exceeded, the strain level would inevitably increase during tensile shear testing, with the induced voids increasing in size and Si diffusion across the interface decreasing, thereby indicating a compromise in the quality of the bond. It was found that the Hulamin benchmark surface preparation, set at 10 µm and 1µm, could be improved by increasing the surface roughness of the core to 15µm while keeping the clad surface finish constant. The findings of this research could be of significant value to Hulamin in the improvement of the quality and cost of the end product under consideration.